In Vitro Inactivation of SARS-CoV-2 Using Gamma Radiation. (September 2020) - Leung, Anders; Tran, Kaylie; Audet, Jonathan; Lavineway, Sherisse; Bastien, Nathalie; Krishnan, Jay
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is classified as a Risk Group 3 pathogen; propagative work with this live virus should be conducted in biosafety level-3 (BSL-3) laboratories. However, inactivated virus can be safely handled in BSL-2 laboratories. Gamma irradiation is one of the methods used to inactivate a variety of pathogens including viruses. Objective: To determine the radiation dose required to inactivate SARS-CoV-2 and its effect, if any, on subsequent polymerase chain reaction (PCR) assay. Methods: Aliquots of SARS-CoV-2 virus culture were subjected to increasing doses of gamma radiation to determine the proper dose required to inactivate the virus. Real-time quantitative polymerase chain reaction (RT-qPCR) data from irradiated samples was compared with that of the non-irradiated samples to assess the effect of gamma radiation on PCR assay. Results: A radiation dose of 1 Mrad was required to completely inactivate 10 6.5 TCID50 /ml of SARS-CoV-2. The influence of gamma radiation on PCR sensitivity was inversely related and dose-dependent up to 0.5 Mrad with no further reduction thereafter. Conclusion: Gamma irradiation can be used as a reliable method to inactivate SARS-CoV-2 with minimal effect on subsequent PCR assay.